2022
DOI: 10.1002/alr.22941
|View full text |Cite
|
Sign up to set email alerts
|

Are nonsteroidal anti‐inflammatory drugs effective enough for postoperative pain control after functional endoscopic sinus surgery and septoplasty? A randomized, controlled study

Abstract: Background Endoscopic sinus surgery (ESS) and septoplasty are commonly performed procedures without standardized postoperative pain regimens. There is reluctance to prescribe opioids for postoperative pain given their potential for abuse. Nonsteroidal anti‐inflammatory drugs (NSAIDs) have been demonstrated to reduce or even obviate the need for opioid pain medications after otolaryngologic surgeries, but prospective validation is lacking. Methods A randomized, controlled study comparing the efficacy of diclofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Overall, nine out of 15 RCTs demonstrated a low risk of bias 25,28–30,32,33,35,37,38 . Four trials demonstrated a high risk of bias due to missing outcome data 24,27,34,36 . A high risk of bias in measurement of outcome was detected in four trials 24,26,31,36 .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Overall, nine out of 15 RCTs demonstrated a low risk of bias 25,28–30,32,33,35,37,38 . Four trials demonstrated a high risk of bias due to missing outcome data 24,27,34,36 . A high risk of bias in measurement of outcome was detected in four trials 24,26,31,36 .…”
Section: Resultsmentioning
confidence: 96%
“…Fifteen RCTs enrolled a total of 1210 patients (median 75 patients, range 28 to 150). Six studies were carried out in Turkey 25,29–31,35,37 and five were conducted in the United States 24,27,33,34,36 . The rest of the studies were conducted in China, 26,38 Italy, 32 or Egypt 28 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Recently, research in head and neck cancer, rhinology, and sinus surgery suggest that alternative pain management therapies like acetaminophen, nonsteroidal anti-inflammatory drugs (NSAIDs), or steroids adequately treat pain and maintain patient satisfaction postoperatively. [20][21][22][23][24][25][26][27][28][29][30] However, less evidence validates these therapies in otology.…”
mentioning
confidence: 99%